Changes in breathing pattern and cycling efficiency as a result of training with Added Respiratory Dead Space Volume - Hebsiz, P.; Hebisz, R.; Zaton, M. (Human Movement, 2013)
Purpose. The aim of this study was to evaluate the impact of training with added respiratory dead space volume (ARDSV) on changes in a breathing pattern and cycling efficiency. Methods. Twenty road cyclists were equally divided into an experimental (E) and control (C) group. All of them were involved in a training program that included endurance training (at moderate intensity) and interval training (at maximal intensity). During semi-weekly endurance training, ARDS V (1000cm3 tube) was introduced in the experimental group. Respiratory parameters, including, among others, oxygen uptake (VO2), carbon dioxide excretion (VCO2), end-tidal partial pressure of carbon dioxide (PETCO2), pulmonary ventilation (VE), tidal volume (TV) and total work done during the tests (W), were measured before and after the experiment by a progressive and continuous test. Results. Higher PETCO2 and TV in both groups during the progressive and continuous tests were observed. VCO2 increased in group E during continuous test, while for group C only in the first four minutes of the test. VO2 and VE increased only in group E during submaximal and maximal exercise. Total work increased during the continuous test in both groups (significantly higher in group C than E). However, total work during the progressive test increased only in group E. Conclusions. Training with ARDSV improved exercise capacity at maximal effort and was associated with an increase in maximal oxygen uptake. On the other hand, this type of training lead to a decrease in cycling efficiency, reducing in effect the benefits associated with an increase in VO2 max and reducing the ability to perform submaximal effort